Human cerebral malaria: association with erythrocyte rosetting and lack of anti-rosetting antibodies. - Carlson, J; Helmby, H; Hill, A; Brewster, D; Greenwood, B; Wahlgren, M (1990)
Plasmodium falciparum isolates from 24 Gambian children with cerebral malaria and 57 children with mild forms of the disease were assessed for their ability to form erythrocyte rosettes. All isolates from the children with cerebral malaria were able to form rosettes, whereas those from children with mild forms of the disease did not form rosettes, or had a significantly lower rosetting rate. Plasma of children with cerebral malaria lacked anti-rosetting activity, whereas plasma of children with mild disease could often disrupt rosettes in vitro. A monoclonal antibody to P falciparum histidine rich protein (PfHRP1/KP/KAHRP) disrupted rosettes of many of the isolates in vitro indicating that the rosetting ligand is relatively conserved compared with ligands associated with endothelial cytoadherence. The findings strongly support the hypothesis that erythrocyte rosetting contributes to the pathogenesis of cerebral malaria and suggest that anti-rosetting antibodies protect against cerebral disease.